Analysis of Marketing Communication Effectiveness Social media Instagram Global Radio at the 2023 Globalkustik Event - Aliansyah, Riko; Wulandari, Astri (Fakultas Ekonomi Universitas Garut, 2024)
The rapid development of social media has become a driving force for economic actors, both in the product and service sector, to carry out marketing through social media or marketing on social networks. This can be seen from the number of social media users who are increasing every year with the various social networking platforms used. An example of social media marketing that is widely used is Instagram. Global Radio is a radio station in Jakarta and Bandung broadcasting popular songs, celebrity news, sports, the latest movies and fashion. In this case, Global Radio promotes via Instagram because it is considered quite effective in communicating with its followers. However, @884globalradio subscribers still do not understand the content provided, such as explanations of the latest entertainment news, Indonesian music shows and others. Therefore, this study aims to determine the effectiveness of social media marketing communications on Instagram Global Radio. Data collection was carried out by distributing questionnaires to 100 respondents. Data analysis in this study used quantitative descriptive analysis. The results of this study are that the overall ratio achieved by researchers on social media marketing variables including context, communication, collaboration, and connection is 89.42%. This explains why the effectiveness of social media marketing via Instagram @884globalradio is considered very good.